Pharmacological Mechanism of Herbal Interventions for Bipolar Disorder - Singh, Abhinav; Sarwat, Maryam; Gupta, Sangeetha (Current Pharmaceutical Design, 2024)
Bipolar disorder is a neuropsychiatric disease characterized by an abundance of undesired ideas and thoughts associated with recurrent episodes of mania or hypomania and depression. Alterations in the circuits, including the prefrontal cortex, striatum, and limbic system, regulate mood and cause variation in several crucial neurotransmitters, including serotonin, dopamine, GABA, and glutamate. Imbalances in dopamine levels have been implicated in the manic phase, while variance in serotonin is linked to depressive episodes. The precise pathophysiology of bipolar disorder is still unknown. Though different treatments are available, like lithium, risperidone, valproic acid, etc., which are widely used, they come with certain limitations, including narrow therapeutic index, hypothyroidism, weight gain, extrapyramidal symptoms, etc. The interest in herbal- based treatments for bipolar disorder arises from the desire for alternative, potentially more natural, and holistic approaches with fewer side effects. The current review focuses on the potential effects of herbal drugs and their derivatives to alleviate the symptoms of bipolar disorder.
Keywords: depression